Measurement of the atmospheric muon spectrum from 20 to 3000 GeV - Dova, María Teresa (2004)
The absolute muon flux between 20 and 3000 GeV is measured with the L3 magnetic muon spectrometer for zenith angles ranging from 0º to 58º. Due to the large exposure of about 150 m2 sr d, and the excellent momentum resolution of the L3 muon chambers, a precision of 2.3% at 150 GeV in the vertical direction is achieved. The ratio of positive to negative muons is studied between 20 and 500 GeV, and the average vertical muon charge ratio is found to be 1.285 ± 0.003(stat.)± 0.019(syst.).